PENERAPAN STANDAR PELAYANAN PUBLIK DALAM PEMBUATAN BUKU NIKAH DI KUA KOTA MATARAM - Winengan, Winengan (LP2M IAIN Mataram, 2014)
Public service standard, a set of guidance which has been defined in several laws, has reflected publicâs enthusiasm upon all government institution, it so does to the local office of religious affairs of which the people have wished to increase its public service standard. The facts however, show that it is quite hard to be applied due to some obstacles and the application itself does not meet a minimum standard. Based on these phenomena this research is conducted. The subjects are the officers in local office of religious affairs in the City of Mataram. These subjects are determined through purposive sampling. The result shows that, first, the application of public service standard is necessarily realized by the people so its importance has been recognized in order to improve public service quality. Second, the existence of different perceptions between the officers and the people who use the service in term of the policy which become a guidance to apply service standard becomes the predicament to present high quality service to the people. Socialization effort, however, before the policy is carried out become a supportive factors for the officers to improve public service quality.